The long-term outcome of orthostatic tremor. Issue 2 (13th March 2015) - Ganos, Christos; Maugest, Lucie; Apartis, Emmanuelle; Gasca-Salas, Carmen; Cáceres-Redondo, María T; Erro, Roberto; Navalpotro-Gómez, Irene; Batla, Amit; Antelmi, Elena; Degos, Bertrand; Roze, Emmanuel; Welter, Marie-Laure; et al.
Abstract : Objectives: Orthostatic tremor is a rare condition characterised by high-frequency tremor that appears on standing. Although the essential clinical features of orthostatic tremor are well established, little is known about the natural progression of the disorder. We report the long-term outcome based on the largest multicentre cohort of patients with orthostatic tremor. Methods: Clinical information of 68 patients with clinical and electrophysiological diagnosis of orthostatic tremor and a minimum follow-up of 5 years is presented. Results: There was a clear female preponderance (76.5%) with a mean age of onset at 54 years. Median follow-up was 6 years (range 5–25). On diagnosis, 86.8% of patients presented with isolated orthostatic tremor and 13.2% had additional neurological features. At follow-up, seven patients who initially had isolated orthostatic tremor later developed further neurological signs. A total 79.4% of patients reported worsening of orthostatic tremor symptoms. These patients had significantly longer symptom duration than those without reported worsening (median 15.5 vs 10.5 years, respectively; p=0.005). There was no change in orthostatic tremor frequency over time. Structural imaging was largely unremarkable and dopaminergic neuroimaging (DaTSCAN) was normal in 18/19 cases. Pharmacological treatments were disappointing. Two patients were treated surgically and showed improvement. Conclusions: Orthostatic tremor is a progressive disorder with increased disability although tremor frequency is unchanged over time. In most cases, orthostatic tremor represents an isolated syndrome. Drug treatments are unsatisfactory but surgery may hold promise.